Drone-borne sensing of major and accessory pigments in algae using deep learning modeling. Issue 1 (31st December 2022) - Pyo, JongCheol; Hong, Seok Min; Jang, Jiyi; Park, Sanghun; Park, Jongkwan; Noh, Jae Hoon; Cho, Kyung Hwa
ABSTRACT: Intensive algal blooms increasingly degrade the inland water quality. Hence, this study aimed to analyze the algal phenomena quantitatively and qualitatively using synoptic monitoring, algal pigment analysis, and a deep learning model. Water surface reflectance was measured using field monitoring and drone hyperspectral image sensing. The algal experiment conducted on the water samples provided data on major pigments including chlorophyll-a and phycocyanin, accessory pigments including lutein, fucoxanthin, and zeaxanthin, and absorption coefficients. Based on the reflectance and absorption coefficient spectral inputs, a one-dimensional convolutional neural network (1D-CNN) was developed to estimate the concentrations of the major and minor pigments. The 1D-CNN could model periodic trends of chlorophyll-a, phycocyanin, lutein, fucoxanthin, and zeaxanthin compared to the observed ones, with R 2 values of 0.87, 0.71, 0.76, 0.78, and 0.74, respectively. In addition, major and secondary pigment maps developed by applying the trained 1D-CNN model to the processed drone hyperspectral image inputs successfully provided spatial information regarding the spots of interest. The model provided explicit algal biomass information using the estimated major pigments and implicit taxonomical information using accessory pigments such as green algae, diatoms, and cyanobacteria. Therefore, we provide strong evidence of the extendibility of deep learning models for analyzing various algal pigments to gain a better understanding of algal blooms.